Isolation of 2, 5-diketopiperazines from Lysobacter capsici AZ78 with activity against Rhodococcus fascians. Issue 23 (2nd December 2021) - Cimmino, Alessio; Bejarano, Ana; Masi, Marco; Puopolo, Gerardo; Evidente, Antonio
Abstract: Inhibitory activity of the biocontrol bacterial strain Lysobacter capsici AZ78 is related to the production of cyclo(l -Pro-l -Tyr), a 2, 5-diketopiperazine with in vitro and in vivo toxic activity against Phytophthora infestans and Plasmopara viticola. Further investigation of culture filtrate organic extracts showed its ability to produce other 2, 5-diketopiperazines. They were isolated and identified by spectroscopic ( 1 H NMR and ESIMS) and physic (specific optical rotation) methods as cyclo(l -Pro-l -Val), cyclo(d -Pro-d -Phe), cyclo(l -Pro-l -Leu), and cyclo(d -Pro-l -Tyr). When tested against the phytopathogenic Gram-positive bacterium Rhodococcus fascians LMG 3605, cyclo(l -Pro-l -Val) showed a toxic activity similar to chloramphenicol at a comparable concentration. Overall, these data suggest that 2, 5-diketopiperazines represent a class of metabolites characterizing the metabolome of L. capsici AZ78. Furthermore, the toxic activity showed by cyclo(l -Pro-l -Val) against R. fascians LMG 3605 broaden the spectrum activity of 2, 5-diketopiperazines against phytopathogenic microorganisms enforcing their potential development as biopesticides.